Relationship Emotional Intelligence with Conflict Management in Employees of PT. Aspacindo Kedaton Motor - Farida Hanum Siregar (Budapest International Research and Critics University, 2020)
The aim of the study is to find out the relationship emotional Intelligence with Conflict Management in Employees of Pt. Aspacindo Kedaton Motor. The research approach used in this study is a quantitative approach using correlation or relationship tests. Correlation research is research that aims to investigate the extent to which variations in one variable are related to variations in one or more other variables. The result of research on employees who have high conflict management and emotional intelligence are also classified as high. This can be seen from the SD results of 6.056, the hypothetical mean value of conflict management at 62.5, and the empirical mean of 74.66. Furthermore, the results of elementary emotional emotional intelligence amounted to 10.38, the mean hypothetical value was 72.5 and the empirical mean was 88.82.